Minimal Nonnegative Solution of Nonlinear Impulsive Differential Equations on Infinite Interval. (2nd August 2010) - Zhang, Xuemei; Yang, Xiaozhong; Feng, Meiqiang
Abstract : The cone theory and monotone iterative technique are used to investigate the minimal nonnegative solution of nonlocal boundary value problems for second-order nonlinear impulsive differential equations on an infinite interval with an infinite number of impulsive times. All the existing results obtained in previous papers on nonlocal boundary value problems are under the case of the boundary conditions with no impulsive effects or the boundary conditions with impulsive effects on a finite interval with a finite number of impulsive times, so our work is new. Meanwhile, an example is worked out to demonstrate the main results.